Employees’ Innovative Work Behavior Model in Electrical and Electronics Industry at Industrial Estate of Chonburi Province - Sunut, Wachapong; Luekitinan, Wannapa; Ingard, Apinya (KKBS Journal of Business Administration and Accountancy, 2020)
The objectives of this research were to develop and inspect causal model of employees’ innovative work behavior in electrical and electronics industry at industrial estate of Chonburi province with empirical data. The sample in this study was employees in supervisor level of electrical and electronics industry at industrial estate, Chonburi province. The 300 samples were obtained from infinite population and considered by number of observed variables. Data were analyzed by using Structural Equation Model (SEM). The results of the study showed that organizational structure, organizational culture and knowledge sharing had direct effect on the employees’ innovative work behavior. Organizational structure and the organizational culture had indirect effects on employees’ innovative work behavior mediated by knowledge sharing. Leader had indirect effect on employees’ innovative work behavior mediated by organizational structure, organizational culture and knowledge sharing. In addition, leader, organizational structure, organizational culture and knowledge sharing could predict employees’ innovative work behavior in electrical and electronics industry at industrial estate of Chonburi province. The predictive ability is 38 percent (R2 = 0.38). Therefore, for employees’ innovative work behavior promotion, leaders must to play a critical role to designing work structure, work culture, and work knowledge sharing activities.